2017
DOI: 10.1111/apt.14345
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of osteoporotic fractures in patients with Barrett's oesophagus: a population‐based nested case‐control study

Abstract: Summary BACKGROUND Proton pump inhibitors (PPI) are inconsistently associated with osteoporotic fractures. Barrett’s oesophagus patients are treated with high PPI doses for prolonged periods, but there is limited data on the incidence of osteoporosis and fractures in them. AIM In this study, we aimed to estimate the incidence of (and risk factors for) low bone mass (osteoporosis and/or osteopenia) related fractures in a population-based Barrett’s oesophagus cohort. METHODS All subjects with Barrett’s oeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…Several studies reported an association between GERD and vertebral fractures or kyphosis [ 256 , 257 , 258 ]. The most recent publications, however, did not confirm that GERD and decreased BMD are linked [ 117 ], neither that the incidence of OFs is higher among subjects with BO [ 259 ] (Kumar S 2017). As in the total population, older age, female gender and a higher comorbidity index were the independent risk factors for OFs in patients with BO.…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
“…Several studies reported an association between GERD and vertebral fractures or kyphosis [ 256 , 257 , 258 ]. The most recent publications, however, did not confirm that GERD and decreased BMD are linked [ 117 ], neither that the incidence of OFs is higher among subjects with BO [ 259 ] (Kumar S 2017). As in the total population, older age, female gender and a higher comorbidity index were the independent risk factors for OFs in patients with BO.…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
“…If PPIs have any effects on bone, they are likely to be systemic. 4 Other fractures among the study population were not reported. The negative results reported do not necessarily mean that there was no association between PPI use and other fractures.…”
Section: Editorsmentioning
confidence: 96%
“…Several previous studies have found association between PPI use and an increased risk of hip fracture [12][13][14][15][16] but there are also studies which did not find an association. [17][18][19] According to a novel meta-analysis, the risk seems to be modestly increased (RR = 1.26; 95% CI 1. 16-1.36), albeit the studies are heterogeneous.…”
Section: Introductionmentioning
confidence: 99%